Individualistic and collective causal knowledge structures for understanding sequential and emergent processes - Chi, Michelene T. H. (Frontiers in Education, 2023)
This paper presents a unifying account for why many biological, ecological and other science processes that are taught in school curricula and those occurring in our everyday environment (such as the spread of Covid19) are particularly difficult for students to understand. These often-misconceived processes are Emergent processes. The hypothesis is that students bring the perspective of Individualistic (a form of linear) thinking suitable for understanding Sequential processes, to explain Emergent processes, instead of the more appropriate perspective of Collective (a form of systems) thinking, thereby resulting in misunderstanding. This paper describes a framework called PAIR-C that defines the causal knowledge structures underlying both Individualistic and Collective thinking needed for understanding many science processes. PAIR-C explains why students generate misconceptions; shows how the Collective causal structure can help understand many Emergent processes; and suggests a new instructional approach.